2024
DOI: 10.1186/s12961-024-01121-x
|View full text |Cite|
|
Sign up to set email alerts
|

A rapid review to inform the policy and practice for the implementation of chronic disease prevention and management programs for Aboriginal and Torres Strait Islander people in primary care

Uday Narayan Yadav,
Jasmine Meredith Davis,
Keziah Bennett-Brook
et al.

Abstract: Background More than 35% of Aboriginal and Torres Strait Islander adults live with cardiovascular disease, diabetes, or chronic kidney disease. There is a pressing need for chronic disease prevention and management among Aboriginal and Torres Strait Islander people in Australia. Therefore, this review aimed to synthesise a decade of contemporary evidence to understand the barriers and enablers of chronic disease prevention and management for Aboriginal and Torres Strait Islander People with a v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(349 reference statements)
0
2
0
Order By: Relevance
“…This review suggested several strategies to overcome challenges to its implementation (e.g., securing buy-in from key clinician and administration stakeholders, desiring clearly defined management approaches that include triage, assessment of cancer case complexity, the roles of clinicians and clinical staff, and acknowledging that the standard of care cannot be universally applied without the consideration of the variations across hospitals and clinics) [ 33 ]. Another review [ 34 ] summarized the enablers of chronic disease prevention and management for the Aboriginal people in Australia (e.g., culturally acceptable and safe services, patient–provider partnerships, primary healthcare service attributes, and clinical care pathways). This review emphasized the need to enable place-based partnerships across patients, providers, and policymakers to develop strategies that align with local community priorities as another system factor [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review suggested several strategies to overcome challenges to its implementation (e.g., securing buy-in from key clinician and administration stakeholders, desiring clearly defined management approaches that include triage, assessment of cancer case complexity, the roles of clinicians and clinical staff, and acknowledging that the standard of care cannot be universally applied without the consideration of the variations across hospitals and clinics) [ 33 ]. Another review [ 34 ] summarized the enablers of chronic disease prevention and management for the Aboriginal people in Australia (e.g., culturally acceptable and safe services, patient–provider partnerships, primary healthcare service attributes, and clinical care pathways). This review emphasized the need to enable place-based partnerships across patients, providers, and policymakers to develop strategies that align with local community priorities as another system factor [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another review [ 34 ] summarized the enablers of chronic disease prevention and management for the Aboriginal people in Australia (e.g., culturally acceptable and safe services, patient–provider partnerships, primary healthcare service attributes, and clinical care pathways). This review emphasized the need to enable place-based partnerships across patients, providers, and policymakers to develop strategies that align with local community priorities as another system factor [ 34 ]. Further in-depth research is warranted to comprehend these identified system issues of implementing the 4Ms Framework.…”
Section: Discussionmentioning
confidence: 99%